2006
DOI: 10.3354/ame042063
|View full text |Cite
|
Sign up to set email alerts
|

Do temperature–food interactions matter? Responses of production and its components in the model heterotrophic flagellate Oxyrrhis marina

Abstract: The consequence of interactions between temperature and food concentration for protistan population dynamics and estimates of aquatic productivity are relatively unknown, primarily because we lack adequate parameters for models. Here, using the heterotrophic flagellate Oxyrrhis marina Dujardin, we demonstrate the importance of considering temperature and food concentration in combination, to determine the responses of grazing rate, specific growth rate, cell volume, specific production and yield. Specific grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 51 publications
7
64
1
Order By: Relevance
“…This supports the conclusions of Kimmance et al (2006) who indicated, also using O. marina, that temperaturedependent gross growth efficiency has non-intuitive interactions with prey abundance. Consequently, we strongly recommend that modelling efforts on population dynamics of microbial eukaryotes, at the very least, consider variable assimilation efficiency and that laboratory studies should be directed at parameterising such responses.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This supports the conclusions of Kimmance et al (2006) who indicated, also using O. marina, that temperaturedependent gross growth efficiency has non-intuitive interactions with prey abundance. Consequently, we strongly recommend that modelling efforts on population dynamics of microbial eukaryotes, at the very least, consider variable assimilation efficiency and that laboratory studies should be directed at parameterising such responses.…”
Section: Discussionsupporting
confidence: 79%
“…It may seem that the scatter of our data is high, but it is typical for estimates of functional and numerical responses of protozoa (for example, Kimmance et al, 2006), and by performing many measurements across the prey range, especially with a focus on lower prey abundances, it is possible to obtain powerful, average estimates of parameters associated with the functional and numerical responses (Montagnes and Berges, 2004). Following this procedure, we have established functional and numerical responses that reveal significant differences in their parameters (Figure 3).…”
Section: Multiple Predator Responsesmentioning
confidence: 99%
See 3 more Smart Citations